MODULAR OUTDOOR FURNITURE PRODUCT FOR NEW NORMAL PUBLIC SPACE (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2025)
The limitation of shared activities in public spaces during the New Normal period requires flexible, multi-functional furniture that can be applied in public spaces. Outdoor modular furniture that can be flexibly modified to avoid spreading the virus through surfaces is required to add value to the public outdoor facility. Outdoor modular furniture with cellular lightweight concrete (CLC) as its material has been developed to be used in public space sitting areas. The modular furniture produced from this study can function as a sitting, playing and working facility with various arrangements in its geometrical form. The furniture can be used by adult users and children with the dimensions that refer to both variants of the user. The design had been made into a 1:1 scale prototype to produce compositions that can be used by adults and children for various activity. The prototype had also been tested for two years in outdoor public facilities. The test results showed that it is necessary to improve the material weight, give more rounded corners, improve the finishing as well as the construction process.